Remarks on Macrobiotus furciger Murray, 1906 and description of three new species of the furciger group (Eutardigrada, Macrobiotidae) - Binda, Maria Grazia; Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2005)
Macrobiotus furciger Murray, has been considered a probable cosmopolitan species. The authors examined specimens named M. furciger from two subantarctic areas from New Zealand, and from South Africa and noted that in the subantarctic area two species are present: M. furciger and a new species here described and named Macrobiotus aradasi sp. nov. The specimens from New Zealand belong to a different species here described and named Macrobiotus divergens sp. nov., and the specimens from South Africa belong to a third new species here described and named Macrobiotus sicheli sp. nov. The authors also hypothesize that the records of Macrobiotus furciger from Andamane Islands and from Europe may refer to different species.